EFEKTIVITAS INSEKTISIDA NABATI DAUN SALAM (SYZYGIUM POLYANTHUM) TERHADAP MORTALITAS NYAMUK AEDES AEGYPTI - Ana Windari; Mimatun Nasihah; Nur Lathifah Syakbanah (Dian Nuswantoro Semarang, 2021)
Dengue Hemorrhagic Fever (DHF) is an acute disease in the form of dengue virus infection which is spread through mosquito bites. The use of synthetic insecticides actually causes negative effects on the environment, so another alternative is needed, namely the use of bay leaf vegetable insecticides. The purpose of this study was to determine the effectiveness of bay leaf insecticide (Syzygium polyanthum) as an insecticide against the mortality of Aedes Aegypti mosquitoes with the liquid electric method. This study used a quasi-experimental (quasi-experimental) design with a completely randomized design (CRD) method where the experiment was conducted on 150 mosquitoes in 5 treatments and 3 replications. The results of the percentage of bay leaf solution (Syzgium polyanthum) which has the largest number of mosquito mortality at a concentration of 80 ml/200 ml of water with a mortality percentage of 60%. The result of probit LC50 analysis of bay leaf solution was 64,315 g/ml. The higher the concentration of the solution given, the greater the number of mosquito mortality. It is necessary to modify the right tools and methods to make a solution of bay leaf (Syzgium polyanthum) so that it is more effectively applied in the community.Keywords: bioinsecticide, bay leaf, liquid electric, mortality, Aedes aegypti